Importancia de la tecnología para la gestión áulica de los docentes de la Unidad Educativa Delia Ibarra de Velasco-ccf del cantón Pujilí en el año lectivo 2014 – 2015 - Caisaluisa Balseca, Gloria Liliana (2015)
This research was conducted in order to know the technology importance on classroom management which allowed improving educational quality and warmth under the teachers’ guide at "Delia Ibarra de Velasco-CCF" Education Unit. Technology has provided an existing social change. Barriers were found on the use and application of many technological tools as educational resources. The tools facilitate the teachers’ work in the teaching-learning process. This research was conducted in order to improve the skills and creativity of teachers. Also, it allowed to know the teachers’ attitudes and skills towards technology and its various forms of learning that today is applied. It was a challenge sensitize teachers to accept that technology is an important part in the education system. To improve teachers’ learning given through a classroom management’s technology training workshop. Likewise, the workshop offers the technological elements implementation which was developed as a teaching tool on classroom management.